Cigarette Smoking, Genetic Variants in Carcinogen-metabolizing Enzymes, and Colorectal Cancer Risk - Cleary, Sean P.; Cotterchio, Michelle; Shi, Ellen; Gallinger, Steven; Harper, Patricia (American journal of epidemiology, 2010)
The risk of colorectal cancer associated with smoking is unclear and may be influenced by genetic variation in enzymes that metabolize cigarette carcinogens. The authors examined the colorectal cancer risk associated with smoking and 26 variants in carcinogen metabolism genes in 1,174 colorectal cancer cases and 1,293 population-based controls recruited in Canada by the Ontario Familial Colorectal Cancer Registry from 1997 to 2001. Adjusted odds ratios were calculated by multivariable logistic regression. Smoking for >27 years was associated with a statistically significant increased colorectal cancer risk (adjusted odds ratio (AOR) = 1.25, 95% confidence interval (CI): 1.02, 1.53) in all subjects. Colorectal cancer risk associated with smoking was higher in males for smoking status, duration, and intensity. The CYP1A1-3801-CC (AOR = 0.47, 95% CI: 0.23, 0.94) and CYP2C9-430-CT (AOR = 0.82, 95% CI: 0.68, 0.99) genotypes were associated with decreased risk, and the GSTM1-K173N-CG (AOR = 1.99, 95% CI: 1.21, 3.25) genotype was associated with an increased risk of colorectal cancer. Statistical interactions between smoking and genetic variants were assessed by comparing logistic regression models with and without a multiplicative interaction term. Significant interactions were observed between smoking status and SULT1A1-638 (P = 0.02), NAT2-857 (P = 0.01), and CYP1B1-4390 (P = 0.04) variants and between smoking duration and NAT1-1088 (P = 0.02), SULT1A1-638 (P = 0.04), and NAT1-acetylator (P = 0.03) status. These findings support the hypothesis that prolonged cigarette smoking is associated with increased risk of colorectal cancer and that this risk may be modified by variation in carcinogen metabolism genes.